Gabriele Malaspina, marchese di Fosdinovo Condotte, politica e diplomazia nella Lunigiana del Rinascimento - Patrizia Meli (Scuole di dottorato, 2009)
This book focuses on one of the prime movers in the unification of Lunigiana - a region which at the time was still broken up into a myriad of tiny feudal holdings, almost all in the hands of the various branches of the Malaspina family. The process of unification began in the fifteenth century, when various areas of the region were conquered by Milan and Florence, which also divided between them the hegemony of the remaining independent territories, while Genoa too displayed an interest in expansion in the region. As a result it became crucial for the local lords to manoeuvre between the various forces at play to maintain the independence of their own little states. Among the figures who displayed the greatest dexterity in this was Gabriele Malaspina, who became a leading player on the stage of local history. The book starts by illustrating the period in which Malaspina succeeded in obtaining his political independence, and then goes on to analyse the phase in which his policy came to be characterised by an absolute loyalty to Florence. Finally the book addresses the last part of the Marquis's life, marked by a progressive distancing from the Florentine alliance in favour of other entities, in which he nevertheless always succeeded in maintaining his independence.